PERAN PEREMPUAN DALAM PENCAPAIAN SDGS MELALUI PEMBANGUNAN NASIONAL - Indriastuti, Indriastuti; Hardaningtyas, Dwi; Ikmal, Novita Maulida (Pusat Studi Gender UIN Maulana Malik Ibrahim Malang, 2023)
This research aims to describe the role of women in achieving the SDGs through national development. In the current era, there are many women's groups that are able to take action in public spaces. The method used in this research is a literature study by looking at various data and documents related to the role of women from various sources. The results of this research show that the main role of women in development is in the fields of education, health, labor force participation and issues of violence. In the field of education, women's educational status reached 23.03% in rural areas and 24.14% in urban areas. In the health sector, 64.1% of women have health insurance and 66.78% of women have main jobs in the agriculture, forestry and fisheries, wholesale trade and processing industry sectors. The goal of the SDGs is to end poverty, reduce inequality and protect the environment. In the SDGs, it can be estimated that more than 600 million new jobs need to be created by 2030. Basically, the main principle of the SDGs is to leave no one behind or no one left behind.